The use of e-learning in universities during the Covid-19 pandemic: An institutional theory perspective - Aditya Pandu Wicaksono; Hadri Kusuma; Riana Mahfuroh (Jurnal Cakrawala Pendidikan, 2023)
The Covid-19 pandemic has forced universities to change learning methods from face-to-face learning to online learning. This study aims to determine the effect of institutional pressure (coercive, mimetic, and normative) on the use of online learning in universities. This study uses a quantitative approach with a total sample of 357 respondents consisting of 42 lecturers and 315 university students in Yogyakarta and Central Java. This research employs an online questionnaire as a data collection media. The questionnaires were distributed and filled out by respondents from September 2020 to February 2021. The research shows interesting findings because pressure from regulators (coercive) is not a significant predictor of e-learning use. Whereas mimetic and normative pressures have a positive and significant effect on e-learning. This study also categorizes the findings into two groups i.e., lectures and students. Students assume that coercive, mimetic, and normative significantly pressure universities to use online learning. Whereas the lecturers think that the pressure from the regulator has no significant effect because health issues are the main priority. This study contributes to the literature by providing empirical evidence on the acceptance of e-learning technology during the Covid-19 pandemic.